2013
DOI: 10.1016/j.jprot.2013.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomic analysis of abnormal intramyoplasmic aggregates in desminopathy

Abstract: Desminopathy is a subtype of myofibrillar myopathy caused by desmin mutations and characterized by protein aggregates accumulating in muscle fibers. The aim of this study was to assess the protein composition of these aggregates. Aggregates and intact myofiber sections were obtained from skeletal muscle biopsies of five desminopathy patients by laser microdissection and analyzed by a label-free spectral count-based proteomic approach. We identified 397 proteins with 22 showing significantly higher spectral ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
75
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 50 publications
5
75
0
Order By: Relevance
“…It is possible that mutant filamin C is also present and is precipitating the aggregation phenotype, which could attract other proteins to the complex as well as bystanders. This would be consistent with the Maerkens et al [32] (2013) that filamin C (presumably normal protein sequence) was found in abundance in desminopathy deposits, along with a multitude of other proteins that appear to have also been trapped. It may be the gradual accumulation of these aggregates that are the underlying cause of cardiac muscle tissue failure, with such aggregates only forming in the presence of an abnormal protein, as seen in cardiac amyloidosis associated with missense mutations in the transthyretin (TTR) gene [33] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…It is possible that mutant filamin C is also present and is precipitating the aggregation phenotype, which could attract other proteins to the complex as well as bystanders. This would be consistent with the Maerkens et al [32] (2013) that filamin C (presumably normal protein sequence) was found in abundance in desminopathy deposits, along with a multitude of other proteins that appear to have also been trapped. It may be the gradual accumulation of these aggregates that are the underlying cause of cardiac muscle tissue failure, with such aggregates only forming in the presence of an abnormal protein, as seen in cardiac amyloidosis associated with missense mutations in the transthyretin (TTR) gene [33] .…”
Section: Discussionsupporting
confidence: 90%
“…This has been termed "filaminopathy" similar to the situation in "desminopathy". While that term now applies to a condition with abnormal tissue deposits in patients with DES mutations, including mutant desmin protein (e.g., Maerkens et al [32] , 2013), in early studies it was a descriptive term indicating presence and/ or dominance of desmin in the tissue aggregate, without knowledge of underlying genetic cause. In the family described here, the desmin gene sequence is normal [19] , yet cardiac aggregates containing desmin were seen.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, within the abnormal DRM linked protein inclusions, desmin co-aggregates consistently with numerous proteins, associated directly or indirectly with the desmin network, including αB-crystallin, hsp27, synemin, syncoilin, nestin, plectin, filamin C, hsp72/73, myotilin, dystrophin, utrophin, α & β-dystroglycan, α, β, γ & δ-sarcoglycans, caveolin, dysferlin, actin, actinin, N-CAM, NOS, collagen VI, laminin, β-spectrin, and ubiquitin (reviewed in [7]). Some of these data were recently confirmed by a proteomic analysis of skeletal muscle biopsies of DRM patients which identified 22 proteins significantly over-represented in the aggregates, with desmin and filamin C having the highest spectral index, followed by Xirp2, αB-crystallin, N-RAP, Xin and Hsp27 [28]. On the other hand, besides desmin, human mutations in most of the above proteins and some additional ones (such as myotubularin [29] and the nuclear lamins A/C, emerin and LAP2a), lead to myopathy and cardiomyopathy, strongly suggesting that desmin might be a common denominator in most of these cases, regardless of the mutated protein.…”
Section: Mechanisms Of Desmin Related Disease Developmentmentioning
confidence: 88%
“…41 Furthermore, a quantitative proteomic assessment of aggregates in desminopathy identified filamin C as the second most abundant protein in these aggregates, providing additional support for the role of filamin C as a mediator of cardiomyopathy. 42 The FLNC mutation identified in DCM-AAY02 is located 1bp from a splice-acceptor, is absent from the 1000Genomes database, is predicted to be strongly deleterious by MaxENT, and is not present in an unaffected sibling. While further functional studies are required to confirm the pathogenicity of this variant, these data underscore the utility of having a mutable super gene-set that allows for the interrogation of putative cardiomyopathy genes.…”
Section: Discussionmentioning
confidence: 99%